Interactions between parasites and microbial communities in the human gut - Berrilli, Federica; Di Cave, David; Cavallero, Serena; D'Amelio, Stefano (Frontiers in Cellular and Infection Microbiology, 2012)
The interactions between intestinal microbiota, immune system and pathogens describe the human gut as a complex ecosystem, where all components play a relevant role in modulating each other and in the maintenance of homeostasis. The balance among the gut microbiota and the human body appear to be crucial for health maintenance. Intestinal parasites, both protozoans and helminths, interact with the microbial community modifying the balance between host and commensal microbiota. On the other hand, gut microbiota represents a relevant factor that may strongly interfere with the pathophysiology of the infections. In addition to the function that gut commensal microbiota may have in the processes that determine the survival and the outcome of many parasitic infections, including the production of nutritive macromolecules, also probiotics can play an important role in reducing the pathogenicity of many parasites. On these bases, there is a growing interest in explaining the rationale on the possible interactions between the microbiota, immune response, inflammatory processes and intestinal parasites.